BRANDS, TRUST AND QUALITY IN AGRO‐FOOD PRODUCTION NETWORKS: THE CASE OF LAYER HENS. Issue 3 (September 2016) - Franz, Martin; Rolfsmeier, Sebastian
ABSTRACT: The expansion of primary breeding companies for layer hens has reached a global scale. Two groups of companies, the Dutch Hendrix Genetics BV and the German EW Group GmbH, dominate the trade with layer hens for industrial egg production in most countries of the world. This article aims to identify the main actors of industrial egg production and to analyse the structure of the global layer hen production network. Furthermore, this paper examines the importance of brands and quality within the production network. While the primary breeding level is discussed on a global scale, the secondary breeding level and the egg production is analysed at a national level for Germany. Since the importance of brands is strongly related to the quality of the products and the trust therein, the structure of the layer hen production network in regard to the role of brands and trust is evaluated. For this evaluation, the authors combined the global production network approach with elements of the convention theory.